Sexual Abuse Directed to Children Admitted to Kocaeli University School of Medicine Department of Forensic Medicine 1998-2006 - Çolak, Başar; Karakaya, Işık; Kurtaş, Ömer; Şişmanlar, Şahika Gülen; Biçer, Ümit (The Bulletin of Legal Medicine, 2009)
Child sexual abuse is the abuse of the child, who has not yet completed his/her sexual development, by an adult for sexual arousal. Misdiagnosed sexual abuse is the cause of either suspect’s being punished or harming of unguilt as well as preventing children’s protection. In this study, it was aimed to evaluate child sexual abuse cases with their characteristics and examination periods which are informed to Kocaeli University School of Medicine, Department of Forensic Medicine. Between 1998-2006, the reports and files of cases at the registers of Kocaeli University School of Medicine, Department of Forensic Medicine, examined retrospectively. Fifty cases (3,1%)under the heading of sexual abuse are included in the study. It is determined that 62% of cases are females, 38% of them are males and 60 % of the cases are under the age of 12. It is also determined that suspects are mostly the cases’ acquaintances (70%) and all of suspects are males. In the 36% (n= 18) of the cases, the questions are asked towards physical diagnosis, in 50% (n = 25) of the cases, the questions were oriented towards mental health, while 14% (n=7) of the cases are examined through both physical and mental evaluations. Impairment of mental health which can be considered as the result of sexual abuse are determined in the 60,5% (n=23) of 38 mental-oriented cases. After recent legal arrangement, a significant increase in sexual abuses is observed and recorded in Department of Forensic Medicine. The organisation and functioning of the units connected to the Ministry of Health and Ministry of Justice are considered unsuitable for the evaluation of sexual abuse. Foundation of Center of Sexual Abuse Evaluation would provide early treatment of present or probable pathologies as well as precise diagnosis. Key words: Child, sexual abuse, mental evaluation, child psychiatry